Ageing of rice: A review. (May 2018) - Saikrishna, Aruva; Dutta, Sayantani; Subramanian, Vijayalakshmi; Moses, J.A.; Anandharamakrishnan, C.
Abstract: Ageing is an intricate phenomenon that starts at pre-harvest and lasts until consumption; but incompletely understood till date. During ageing, significant changes occur in the physicochemical, sensory, cooking and pasting properties of rice. Most changes are time and temperature dependent and their effects on grain quality are irreversible; mostly being beneficial. Aged rice has better commercial value, owing particularly to improved milling yield, higher consumer preference in terms of cooked rice texture, flavor and associated parameters. Natural ageing through conventional processes requires undesirably long storage duration, in addition to associated higher operational and maintenance costs of the warehouse. Alternatively, artificial ageing of rice has been investigated by researchers to achieve similar results in lesser time and lower cost. This review discusses the changes that occur during ageing of rice, and the methods for artificial ageing. The exposition attempts to highlight a comparative evaluation of various techniques and their scopes. Important attributes to identify quality aged rice have also been included to provide an in-depth idea about the topic. Highlights: Overview of physicochemical changes in rice during storage. Comparison of accelerated ageing and natural ageing of rice with fresh rice. Treatments available for accelerated ageing of rice. Limitations and scope of work related to ageing of rice.